The prognostic significance of β-Catenin expression in patients with nasopharyngeal carcinoma: A systematic review and meta-analysis - Zhou, Liu-Qing; Shen, Jin-Xiong; Zhou, Tao; Li, Chun-Li; Hu, Yao; Xiao, Hong-Jun (Frontiers in Genetics, 2022)
Background: β-Catenin has been recently identified as a promising novel therapeutic target and prognostic marker in different types of cancer. Here, we conduct a meta-analysis to better clarify the correlation between β-Catenin expression and survival outcomes in nasopharyngeal carcinoma (NPC) patients. Patients/methods: Following the Preferred Reporting Items or Systematic Reviews Meta Analyses (PRISMA) 2020 guidelines, the PubMed, Embase, Web of Science, Cochrane Library, Chinese National Knowledge Infrastructure (CNKI) and Wanfang databases were systematically searched for relevant studies to explore the prognostic significance of β-Catenin in NPC. Pooled hazards ratios (HRs) and 95% confidence intervals (CIs) were used to estimate the association of β-Catenin expression with survival outcomes in NPC patients. Odd ratios (ORs) and 95% CIs for clinicopathological characteristics were also statistically analyzed. Results: Eight studies involving 1179 patients with NPC were ultimately included in the meta-analysis. Pooled analysis indicated that elevated β-Catenin expression was significantly associated with poor OS (HR = 2.45, 95%CIs: 1.45-4.16, P = 0.001) and poor DFS/PFS (HR 1.79, 95%CIs: 1.29–2.49, P= 0.000). Furthermore, β-cadherin was signifcantly associated with higher TMN stages (OR = 5.10, 95% CIs 2.93–8.86, p = 0.000), clinical stages (OR = 5.10, 95% CIs 2.93–8.86, p = 0.000) and lymph node metastasis (LNM) (OR = 5.01, 95% CIs 2.40–10.44, p = 0.000). Conclusions: This study demonstrated that for NPC, patients with elevated β-Catenin expression are more likely to have poor survival.